On willingness to pay for Covid-19 vaccines: a case study from India. Issue 12 (2nd December 2021) - Das, Upasak; Rathore, Udayan; Pal, Rupayan
ABSTRACT: In this paper, using survey data from 1251 respondents from peri-urban parts in the Bhopal district of India, we estimated the willingness-to-pay (WTP) for hypothetical Covid-19 vaccines. We use open-ended questions along with the discrete choice contingent valuation method for two vaccines, one with full efficacy and the other with 70% efficacy. While no major evidence of vaccine hesitancy was observed, we found a WTP of about Rs. 141 ($1.9) for the former type vaccine and about Rs. 116 ($1.6) for the latter. From the contingent valuation method, we found about 71.9% were not willing to spend Rs. 200 ($2.7) or more for the fully effective vaccine, while this figure goes up to 77.8% for the one with 70% efficacy. Estimations from linear and probit regressions suggest that economic indicators were the most important predictors of WTP. Usage of public transport, the number of days that the respondent stepped out for work, and the presence of comorbid individuals in the household were positively associated with the WTP, while pandemic-induced income reduction was negatively correlated. The findings lend support toward the requirement of highly subsidized vaccines, and hence back the recent policy announcement toward the supply of free vaccines to all states.